Ottoman subjects and prisoners of war in the Semirechye Oblast during the First World War - Abdukadyrov, Nurzhigit; Mukhazhanova, Tolkyn; Sabdenova, Gulmira (International journal of Asian studies, 2024)
Amidst the upheavals of the First World War, a considerable number of prisoners of war from the Ottoman Empire found themselves in Russia, resettled primarily in the central regions of the Russian Empire. The regions of Volga, Siberia, Ural, and Western Siberia played host to Ottoman prisoners, who were accommodated in camps and barracks across cities and rural areas. Over time, a noteworthy migration led some prisoners to the territory of modern Kazakhstan, with cities like Samara, Orenburg, and Omsk serving as pivotal points before further dispersion into the central regions of Kazakhstan. As a result, Ottoman citizens found themselves under suspicion and were dispersed akin to prisoners. The Semirechye Oblast (Zhetisu region) emerged as a focal point where both Ottoman subjects and prisoners of war were dispersed during this tumultuous period. This article investigates the political and social dynamics, as well as the fate, of Turkish prisoners of war and citizens within the Semirechye Oblast during the war. The analysis delves into the status of Ottoman Empire subjects who acquiesced to the authority of the Russian Empire, offering insights into the lives of prisoners of war in this specific region.